Management of ocular hypertension following intravitreal dexamethasone implant (ozurdex) - Jason Xiao; Mary Qiu (American Journal of Ophthalmology Case Reports)
Purpose: To evaluate the impact of intravitreal dexamethasone implantation (Ozurdex) on ocular hypertension (OHT) development and characterize its management with non-invasive or minimally-invasive modalities. Results: Chart review was performed for patients who received Ozurdex implantation between September 2016 to September 2023. Patients were excluded if they had ever been diagnosed with neovascular glaucoma or received a different intravitreal corticosteroid prior to Ozurdex injection or 6 months afterwards. The analysis included 171 Ozurdex implants (n = 61 patients, n = 74 eyes) for analysis. Patients were followed for an average of 326 ± 45 days. The rise in IOP was greatest 2- and 3-months post-injection. OHT occurred following 40 (23.3 %) Ozurdex implants. To lower IOP, medical drops were initiated after 17 (10.0 %) implants. Selective laser trabeculoplasty was performed in 2 (1.2 %) cases. Minimally-invasive glaucoma surgeries (MIGS) were utilized in 7 (4.1 %) cases. Patients >60 years old were at increased odds of developing OHT, whereas patients treated for retinal vein occlusion were less likely to develop OHT compared to patients treated for diabetic macular edema. Conclusion: Patient-specific characteristics, including age and treatment indication, may confer different risk for developing OHT following Ozurdex implantation. Ozurdex-induced OHT can be safely and effectively managed using a combination of medical therapy, laser trabeculoplasty, and angle-based MIGS. This study supports an increasing range of alternative approaches for addressing elevated IOP or postponing surgeries linked with higher risks.